Outdoor Social Studies Experiences of Teacher Candidates - Fisun BOZKURT (Anı Publishing, 2021)
This basic qualitative research aims to reveal the meaning of outdoor learning activities experienced by social studies teacher candidates. The study focused on the experiences of teacher candidates using a social constructivist perspective. The study group of this basic qualitative research consists of 16 social studies teacher candidates who took the Special Teaching Methods II course in a state university in the 2018 2019 academic year. The research data were obtained from the semi-structured interview and the observation notes of the researcher. The data were analyzed using the content analysis method. The findings of this study revealed that even just going out of the classroom has educational potential, that outdoor learning facilitates both experiential and participatory learning and creates a more inclusive environment. In addition, in this study, it was found that outdoor learning may develop skills such as problem-solving, critical thinking, perception of space, change and continuity, observation, communication and cooperation which are vital in teaching social studies. Teachers cannot include it in the program without having personal experience in outdoor learning. The prerequisite of all teacher education programs should be learning environments that model the pedagogical expectations of teacher candidates. For this reason, outdoor learning should be accepted and supported as an integral part of the entire school curriculum.